Analisis Inovasi Kurikulum Pembelajaran PAI di SMK Negeri 1 Lemahabang Cirebon - Vilia Fitriarti; Saehu Abas; Muhammad Chabib (Indonesian Journal of Islamic Education Studies (INJURIES), 2023)
The curriculum serves as an educational guideline. The curriculum not only serves as a learning guideline created by the government to be implemented in schools, but also affects the progress of the country through the quality of its education. The purpose of this research is to trace the PAI learning activities at SMK Negeri 1 Lemahabang Cirebon using the established curriculum. The method used is a qualitative approach, because this research focuses on natural, basic, and naturalistic phenomena or symptoms. Qualitative research design with observation, interview, and documentation techniques. The results showed that the PAI curriculum innovation applied at SMK Negeri 1 Lemahabang Cirebon was carried out by utilizing technology, implementing project-based learning, involving local religious communities, and developing creative resources in accordance with religious values. Keywords: Curriculum Innovation; PAI Curriculum; PAI Learning.